(untitled) (Veterinary Science, 2017)
Diseases causcd by the Hantaan virus were known as Haemorrhagic Fever with Renal Syndrome. In 1993 an outbreak caused by Hantavirus was diagnosed in the South West area of the EEUU, but with other characteristics, defining it as Pulmonar Syndrorne for Hantavirus. This syndrome has been identified in differents areas in Argentine . One reservoir involved in the outbreak of the south of the country is in La Pampa. At this first phase, captures were made, rodents were sexed, weighed, identified, being found three individuals of sp Calomys laucha, which is supposed to be the reservoir of the outhreak in Paraguay. As well as this, samples were sem to ANLlS - Malbran, being finally negative to hantavirus. During the year, captures will be continued